Regulation of differentiation and generation of osteoclasts in rheumatoid arthritis - Niu, Qing; Gao, Jinfang; Wang, Lei; Liu, Jiaxi; Zhang, Liyun (Frontiers in Immunology, 2022)
Introduction Rheumatoid arthritis (RA), which affects nearly 1% of the world’s population, is a debilitating autoimmune disease. Bone erosion caused by periarticular osteopenia and synovial pannus formation is the most destructive pathological changes of RA, also leads to joint deformity and loss of function,and ultimately affects the quality of life of patients. Osteoclasts (OCs) are the only known bone resorption cells and their abnormal differentiation and production play an important role in the occurrence and development of RA bone destruction; this remains the main culprit behind RA. Method Based on the latest published literature and research progress at home and abroad, this paper reviews the abnormal regulation mechanism of OC generation and differentiation in RA and the possible targeted therapy. Result OC-mediated bone destruction is achieved through the regulation of a variety of cytokines and cell-to-cell interactions, including gene transcription, epigenetics and environmental factors. At present, most methods for the treatment of RA are based on the regulation of inflammation, the inhibition of bone injury and joint deformities remains unexplored. Discussion This article will review the mechanism of abnormal differentiation of OC in RA, and summarise the current treatment oftargeting cytokines in the process of OC generation and differentiation to reduce bone destruction in patients with RA, which isexpected to become a valuable treatment choice to inhibit bone destruction in RA.